Reporting of Individual Taxpayer Annual Returns with E-Filling for Employees - Hirmaleny, Yenny; Hartutik, Sri; Suprayogi, Suprayogi; Latif, Abdul; Fajar, Nanda Kurnia; Kherani, Evi; Suripto, Suripto; Holiawati, Holiawati (Institut Bisnis dan Informatika Kesatuan, 2024)
The tax socialization activity at PT. Medikarya Utama aimed to enhance employees' understanding and awareness of filing Individual Taxpayer Annual Returns (SPT) through the E-Filing system. E-Filing, an electronic service provided by the Directorate General of Taxes (DJP), offers convenience and efficiency in tax reporting. This activity was held at PT. Medikarya Utama, Cicurug, Sukabumi, involving all company employees. The results showed improvements in tax literacy, technical understanding of E-Filing, and tax compliance levels. Additionally, the program boosted employees’ confidence in independently filing their taxes. However, some challenges were identified, such as limited digital literacy and technology access among certain employees. To address these issues, the company provided targeted assistance, intensive training, and adequate technological facilities at the workplace. This initiative not only positively impacted the employees but also demonstrated the company’s commitment to tax compliance and contributing to state revenue. By enhancing employees’ capacity to utilize E-Filing, PT. Medikarya Utama supports government efforts to promote digital transformation in taxation.